On the metrization - Azram, Mohammad (2010)
In this article, we have studied the concept, property and inter-relationship of being T1-space, discrete space, metrizable space,separable space and topologically totally bounded space with finite,infinite and countable underlying set. With some additional conditions we have established equivalence between T1-space,discrete space, metrizable space, separable space and topologically totally bounded space. At the end we have extended the same to a disjoint (free) union.